1995
DOI: 10.1212/wnl.45.8.1477
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychological pattern of corticobasal degeneration

Abstract: The pattern of cortical and subcortical neuropathologic lesions in corticobasal degeneration (CBD) should predict a specific cognitive profile in this disease. To characterize this profile and to determine its specificity by comparison with progressive supranuclear palsy (PSP) and senile dementia of the Alzheimer's type (SDAT), we used an extensive neuropsychological battery assessing global efficiency, executive functions, various tests of encoding and retrieval, dynamic motor organization, and upper limb pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(124 citation statements)
references
References 15 publications
7
113
1
3
Order By: Relevance
“…The prevalence of this symptom was surprising given the relatively minor impairments on tests of episodic memory and relative paucity of tauopathy in the mesial temporal lobes, a finding observed in other studies. 4,32,33 The distribution of tau pathology was similar to that reported previously in patients with CBS, 2,4,8,13,[34][35][36] suggesting that the predominance of early memory complaints may reflect deficits in strategies for encoding and retrieval, owing to disruption of structures more frequently affected by CBD, including frontotemporal subcortical areas. 15 Previous case series reported a low frequency of detection of classic CBS signs (i.e., asymmetric motor/sensory features, parkinsonism, and/or dystonia) at onset in patients with cognitive presentations of CBD.…”
supporting
confidence: 82%
“…The prevalence of this symptom was surprising given the relatively minor impairments on tests of episodic memory and relative paucity of tauopathy in the mesial temporal lobes, a finding observed in other studies. 4,32,33 The distribution of tau pathology was similar to that reported previously in patients with CBS, 2,4,8,13,[34][35][36] suggesting that the predominance of early memory complaints may reflect deficits in strategies for encoding and retrieval, owing to disruption of structures more frequently affected by CBD, including frontotemporal subcortical areas. 15 Previous case series reported a low frequency of detection of classic CBS signs (i.e., asymmetric motor/sensory features, parkinsonism, and/or dystonia) at onset in patients with cognitive presentations of CBD.…”
supporting
confidence: 82%
“…On the other hand, the AD patients were more impaired in orientation and word recognition than the CBD patients. These features of cognitive impairment are compatible with previously reported findings [8]. In agreement with previous studies [10,[12][13][14], the CBD patients showed greater glucose metabolic asymmetries in the lateral frontal, lateral temporal, central and lateral parieto-occipital regions, in comparison with the normal controls.…”
Section: Discussionsupporting
confidence: 93%
“…We excluded the patients with complications of other neurological disease or evidence of focal brain lesions on MRI. Although the Lang exclusion criteria include cognitive disturbances other than apraxias, language disorders or dementia while the patient remains ambulatory, we did not apply them because CBD patients often manifest cognitive disturbances [2][3][4][5][6][7][8] and because cognitive and cortical impairment was the main focus in the present study. All CBD patients in this study had a markedly asymmetrical onset.…”
Section: Selection Of Subjectsmentioning
confidence: 99%
“…In addition, many reports of neuropsychological performance in patients with ET have highlighted a pattern of attentional and executive dysfunction that is analogous to that observed in neurodegenerative diseases affecting subcortical white matter [Schmidtke and Hull, 2002;Traykov et al 2002;Tierney et al 2001;Doddy et al 1998;Lafosse et al 1997] and basal ganglia structures [Troster et al 2002;Lundervold et al 1994;Pillon et al 1995;Cummings, 1998]. …”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 89%